Pemetaan Cluster Spasial Produksi Perkebunan di Indonesia - Kusuma, Arya Candra; Mawarsari, Ucik (Seminar Nasional Official Statistics, 2025)
Plantation agriculture in Indonesia plays a crucial role in ensuring national food security and driving regional economic development. This study aims to analyze the spatial patterns of plantation production across 38 provinces in Indonesia using the SKATER (Spatial 'K'luster Analysis by Tree Edge Removal) algorithm. It focuses on ten major plantation commodities: oil palm, rubber, cocoa, coffee, tea, coconut, sago, clove, sugarcane, and tobacco, based on 2023 production data. Descriptive analysis reveals substantial variation in production levels across regions and commodities. Spatial clustering, conducted using GeoDa, groups provinces into six distinct clusters with unique production profiles. These findings highlight local commodity specialization and production potential, which can inform more targeted policy interventions. The study contributes to spatially informed development planning and supports Indonesia’s national agenda on food security and regional development in line with the Asta Cita vision and the Golden Indonesia 2045 mission.